Delayed Admission in Neonatal Cholestasis - Setyoboedi, Bagus; Prihaningtyas, Rendi Aji; Winahyu, Anindya Kusuma; Arief, Sjamsul (Universitas Airlangga, 2024)
Delayed diagnosis of cholestasis in neonates remains a problem. Cholestatic jaundice is a pathological condition that requires immediate treatment, such as biliary atresia. This study aims to analyze the characteristics of infants with cholestasis who seek treatment at a tertiary hospital. This study was a cross-sectional study to determine the characteristics of infants with cholestasis treated at the tertiary hospital at Dr. Soetomo General Academic Hospital, Surabaya, East Java, Indonesia. Subjects were collected using medical records using the consecutive method from 2019 to 2021. The inclusion criteria in this study were infants aged >2 weeks who suffered from cholestasis. The age of the 111 infants with cholestasis involved was 4.8 ± 2.9 months old. A total of 27 (24.3%) infants visited the hospital at the age of <2 months, 36 (32.4%) at the age of 2-4 months, but most of them, consisting of 48 (43.2%) infants, came to the hospital at the age of >4 months. Jaundice was present at birth in 23 infants (20.7%), and most infants had jaundice at 1 month of age in 75 infants (67.6%). Most of the infants (75 infants) had jaundice at the age of 1 month but visited the hospital at the age of >4 months. This showed that the late diagnosis of cholestasis in infants was still quite high. This study supports education for early detection of cholestasis in primary healthcare medical personnel, community health workers, and parents.